Penerapan Program Mulāzamah Sebagai Upaya Pengkaderan Pendidik Al-Qur'an (Studi Kasus Pusat Pendidikan Al-Qur'an Al-Mahir Gawanan Colomadu Tahun Ajaran 2016/2017) - Hidayati, Fajar Wahyu; , Drs. Zaenal Abidin, M.Pd (2017)
Al-Qur'an is a holy book of Muslims, a guide for every Muslim in running their lives. Learning it is a compulsory for every Muslim, and a Muslim who is busy in learning and teaching of Qur'an will have an honorable position in the sight of Allah. Al-Quran learning activities include reading, memorizing and understanding it. In learning Quran, the teacher holds a very important role. Moreover, lately the public interest to learn the Qur'an is quite large, therefore more teacher are needed, and not all the teachers really understand the rules of reading the Qur'an. Some of them do not apply the rules of Tajweed in reciting Qur'an. Then there should be recruitment of teachers of Qur'an which is exactly mature in terms of both scholarly and teaching skills. Then the problem is how the implementation of Mulāzamah program as a recruitment of Qur'an Teacher. The Objective of this study is to describe the implementation of Mulāzamah program as a recruitment of Qur'an Teacher. This research is a field research with a qualitative approach. Techniques of collecting data are interviews, observation and documentation. While the method of data analysis uses analysis of descriptive qualitative that is in narrative form or paragraphs and not in the form of number through the process of data collection, data reduction, and display data. Furthermore, the conclusions are taken by deductive method. It is a way of thinking that comes from theory then being matched with data. According to the result of data analysis, it can be concluded that Mulāzamah program implemented in the Al-Mahir Education Center of the Qur'an (PPQ) is a Quran memorizing program for 2 years with the addition of Islamic study. The purpose of this program is to create Qur'an teacher that can contribute for society. The abilities developed in the program is the basic skill to memorize 30 chapters of Qur'an in correct reading, powerfull, and good comprehension. Then the skills of public speaking and leadership, entrepreneurship and supporting capabilities such as design, and teaching skill are trained through Micro Teaching and devotion after completing the study. There are differences in the results of the Mulāzamah program between male and and female students, for the male 80% of students are reaching the target while the female are left behind the target, one reason is the participation of female students in learning at TPA so that when memorizing and learning they have less time. Another obstacle is due to the frequent of change of officials or teachers, therefore the system is changing. Director of Al-Mahir PPQ is working on standard system for Al-Mahir PPQ and continues to monitor the implementation of all programs to run properly. Keywords: Mulāzamah, Recruitment, Qur'an Teacher